Effects of Fermentation on the Physico-Chemical Properties of Marine By-Products: A Review - Shobihah, Hasna Nabila; Andriani, Yuli; Wiyatna, Muhamad Fatah; Iskandar, Iskandar; Zidni, Irfan; Rustama, Mia Miranti (Journal of Coastal and Ocean Sciences, 2025)
Marine by-products hold significant potential to be utilized as raw materials with added value, particularly in producing high-quality and environmentally friendly fish feed. This study aims to review the impact of fermentation on the physical and chemical properties of marine by-products. The method employed is a narrative literature review, referencing scientific literature from databases such as ScienceDirect and Google Scholar. The literature analysis highlights changes in physical structure, such as alterations in color and odor, that contribute to improved feed digestibility. In addition, fermentation also increases nutrient content, including proteins and essential amino acids, and produces bioactive compounds that act as antimicrobials and antioxidants. This study identifies that fermentation reduces waste and enhances its economic value for various applications, such as fish feed and alternative raw materials. Thus, this review provides innovative solutions for marine by-product management while supporting sustainability and efficiency principles in the fisheries industry